Speculations on Black life: the collected writings of William R. Jones - Jones, William R. (Bloomsbury studies in black religion and cultures, 2023)
"Is God a white racist? Posed by William R. Jones in his ground-breaking book of the same name, this question disrupted the theological assumptions that marked Black religious thought from early writings of the 1800s to the formation of Black theology in the 1960s. This book compiles his key and essential writings related to over three decades of critical reflection on race, religion, secularism, and oppression in the United States. Over the course of 30 years, Jones pushed questions and considerations that refined Black theology and that gave greater shape to and understanding of Black philosophers' intervention into issues of racial and structural inequality. His philosophical work, related to the grid of oppression, fosters an approach to the nature and meaning of oppression in the United States, encouraging rational interrogation of structures of injustice and thought patterns supporting those structures. Still relevant today, the straightforward style of communication used by Jones makes these essays easily accessible to a popular audience, while maintaining intellectual rigor making the book also suitable for an academy-based audience"-- Provided by publisher